Angina pectoris: the lipid profile and clinical practice. - Diogo, A N (1997)
After a brief historical synopsis of lipid lowering therapy and coronary artery disease, the actual issues were discussed. The problem of secondary prevention of coronary artery disease was addressed on the basis of the recently published studies. A special emphasis was given to the 4S and CARE studies and their results discussed. The problem of primary prevention in the light of the West of Scotland Study is discussed.